THE IMPORTANCE OF PUBLIC RELATIONS ROLE IN EDUCATIONAL INSTITUTIONS AS A MEANS OF PUBLIC COMMUNICATION (A STUDY ON IMMIGRATION POLYTECHNIC - Hartati, Besse (Journal of Administration and International Development, 2023)
This study aims to explore and analyze the importance of public relations in educational institutions as a means of public communication, with a focus on the Immigration Polytechnic. The presence of public relations in educational institutions is crucial as it serves as the gateway for effective communication between the institution and various stakeholders, including the general public, prospective students, students, faculty, pegawaif, and partners. The research methodology adopted a qualitative approach with in-depth data collection. The researchers utilized various data collection techniques, such as in-depth interviews with the management and public relations pegawaif of the Immigration Polytechnic, surveys among the public to gauge their perceptions of public relations, content analysis of materials published by the institution's public relations, and participatory observation of various public relations activities. The results of the study indicate that public relations at the Immigration Polytechnic plays a strategic role as an effective means of public communication. The function of public relations in disseminating information about programs, facilities, achievements, and various institutional activities contributes to enhancing a positive image and increasing public awareness of the Immigration Polytechnic. Communication established with prospective students, students, faculty, and pegawaif through public relations also strengthens emotional bonds and loyalty to the educational institution. The study also reveals that educational institutions' public relations must be adaptable in facing the challenges of public communication in the digital era. Social media, websites, and other digital platforms become essential for educational institutions' public relations to reach a wider audience Overall, this research provides in-depth insights into the significance of public relations in educational institutions, particularly at the Immigration Polytechnic, as a means of public communication. The findings of this study are expected to contribute to the development of more effective and innovative communication strategies in other educational institutions to enhance their reputation and positive image in the eyes of the public.